Metabolism in the progression and metastasis of brain tumors. (28th July 2022) - Tyagi, Abhishek; Wu, Shih-Ying; Watabe, Kounosuke
Abstract: Malignant brain tumors and metastases pose significant health problems and cause substantial morbidity and mortality in children and adults. Based on epidemiological evidence, gliomas comprise 30% and 80% of primary brain tumors and malignant tumors, respectively. Brain metastases affect 15–30% of cancer patients, particularly primary tumors of the lung, breast, colon, and kidney, and melanoma. Despite advancements in multimodal molecular targeted therapy and immunotherapy that do not ensure long-term treatment, malignant brain tumors and metastases contribute significantly to cancer related mortality. Recent studies have shown that metastatic cancer cells possess distinct metabolic traits to adapt and survive in new environment that differs significantly from the primary site in both nutrient composition and availability. As metabolic regulation lies at the intersection of many research areas, concerted efforts to understand the metabolic mechanism(s) driving malignant brain tumors and metastases may reveal novel therapeutic targets to prevent or reduce metastasis and predict biomarkers for the treatment of this aggressive disease. This review focuses on various aspects of metabolic signaling, interface between metabolic regulators and cellular processes, and implications of their dysregulation in the context of brain tumors and metastases. Highlights: Both malignant brain tumor and metastasis entails variant metabolic traits to survive. Nutrient availability and differential metabolic dependencies affect malignant brain tumor and metastasis progression. Metabolic vulnerability in tumor cell and immune cells determine therapy response. Metabolic interaction in the tumor microenvironment may reveal novel therapeutic targets.